Membangun kesadaran dan perilaku sehat terkait hepatitis A melalui promosi kesehatan berbasis komunitas :: Sebuah studi pemberdayaan komunitas penyedia makanan di sekolah - AGUNG, Yusuf Ratu ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This research was conducted to understand about how to raising awareness and health behavior in Hepatitis A during the community of food provider at school effectively . The subjects of this research are the food providers at school, who providing food for the student and the other school member. There were 30 persons involved in this research. These 30 persons categorized in two main group. The experiment group and the controlled group. This research is an action research, with pretest and posttest design. And use an interactional group discussion as an intervention. There two scales used for gathering data, the awareness scale and the health behavior scale. The data analyzed with Mixed Anova. The statistical data analysis showed that an interactional group discussion with recommendations and agreement that implemented significantly raising the awareness (MD=3,600, p<0,05) and the health behavior for Hepatitis A (MD=1,800, p<0,05) during the food provider community who categorized in experiment group.